Near-infrared speckle contrast diffuse correlation tomography for noncontact imaging of tissue blood flow distribution. (2022) - Mazdeyasna, Siavash; Huang, Chong; Chen, Lei; Irwin, Daniel; Yu, Guoqiang
No abstract available